AME annual conference 20-22 June 2001, University of Bath : delegate information. (Thomas Telford, 2001)
Providing access to engineering content from the past, this is the proceedings of the Association of Municipal Engineers' annual conference held in 2001.
Keywords: Municipal engineering -- Congresses.; elektronické knihy; electronic books